IDENTIFIKASI TELUR SOIL TRANSMITTED HELMINT (STH) PADA TANAH PERSAWAHAN DI DESA SUKODONO MENGGUNAKAN METODE NATIF - Suryani, Elsa Mega; Sunarko, Yuli Novianti; Pradana, Muhammad Sungging; Santoso, Setyo Dwi; Batati, Nadiah Al (Jurnal SainHealth, 2023)
Soil is a mineral material that has several unconsolidated forms which are located on the surface of the earth and have undergone several treatments. Soil-Transmitted Helminth (STH) is an intestinal nematode that in its life cycle requires a soil medium for the infective form to mature. worms are moist soil, shady, and protected from sunlight. This study aims to determine whether there is contamination of "Soil-Transmitted Helminth" eggs and what species are present in the rice fields using the Native method. This examination uses a 2% eosin solution. The sample uses paddy fields in Sukodono Village. Sampling at 3 sampling points with 3 types of samples, the total sample is 9 samples of paddy soil. The research was conducted on April 26-28 2021 at the Parasitology Laboratory, Faculty of Health Sciences, Maarif Hasyim Latif University, Sidoarjo, on 9 samples of paddy soil, the results obtained were 3 types of samples, or 33% of the soil contaminated with worm eggs and 6 types of samples or 66% not contaminated with worm eggs. Keywords: Paddy fields, Soil Transmitted Helminth, Native Method